COUNTERTYPE OF BELGIAN IN HERGĔ THE ADVENTURE OF TINTIN: REPORTER FOR LE PETIT VINGTIEME IN THE CONGO - HERMANTO, ARI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Countertype, Belgians, Congolese, The Adventure Of Tintin, Congo.Comic is one of the literary works created as an entertainment that entertains people who read it. In addition, comic as entertainment can also be primarily used as a means to express the feelings, depict events or criticize events that had happened in a current time. In the comic entitled the Adventure of Tintin: Reporter for Le PetitVingtieme in the Congo there are some countertypes appear in the story inserted by the writer. In this research, the researcher presented two problems of the studies, the first is whatthe countertypes done by the Belgian are and second is how the social condition influences the story of the comic is. Those problems of study will be the object of this research.In this research, the researcher used sociological approach to know the socialcondition in the country as the setting of the comic. The researcher used theory ofstereotype from Nachbar and Lause in a book entitled Popular Culture: An Introductory Text (1992). This theory explains about how the image of a group is created.In findings, the researcher found that things or actions done by the Belgian in the comic is to show that they are kind people. Those are in contrast from the reality where in fact Belgium was the colonizers.The researcher suggests the next researcher to discuss the politic issue using theory of hegemony. It is will be discus about the portrayal of Tintin as representation of Belgian which always helps the Congolese in the comic. Those things are used to erase the bad experiences and used by Belgium to keeps the relation between Congo,because Congo has so many nature resources that will be taken by Belgium and willgives benefit for Belgium.